Opportunities for Cottage Industries and Entrepreneurship from Banana Food Processing (SAARC Journal of Agriculture, 2026)
In the international agricultural market, India is the world's leading producer of bananas. In terms of area and productivity, bananas are the third-largest fruit crop in India. It makes up 13% of the entire area and 33% of the fruit production. The majority of the banana production of the world is in India and consumed by Indian people. The consumption banana in mainly as fresh fruit and only 5% of the crop is consumed in processed form, offering plenty of room for processing in the future. Maharashtra is the second largest producer of banana fruits. It ranks first in productivity and second in terms of area under banana fruits. It accounts for 37% of total banana fruit production. Jalgaon is the highest banana producing district in the Maharashtra with around 70% of the state production. Banana is a rich source of vitamins B and carbohydrate. Additionally, it is a good source supplier of potassium, phosphorus, calcium, and magnesium. The fruit is simple to digest with cholesterol and fat-free. Banana fruit crop is fully utilized in the form of fruits, stems and leaves. From Banana fruit crop providing lots of opportunities to cottage industries and private entrepreneurs to make various items from fruits, stems and leaves with small resources machinery and investment.SAARC J. Agric., 23(2): 9-16 (2025)